Prioritizing the healthcare needs of Latinos with mental illness. Issue 1 (2nd January 2017) - Corrigan, Patrick W.; Torres, Alessandra; Lara, Juana L.; Sheehan, Lindsay; Larson, Jonathon E.; ,
ABSTRACT: Latinos with serious mental illness have higher morbidity and mortality rates than same age peers. In this paper, we review findings of a community based participatory research project meant to identify important health needs of this group, barriers to these needs, solutions to the barriers and the promise of peer navigators as a solution. Findings from a prior qualitative study yielded 84 themes related to needs, barriers and solutions. These findings were transposed into individual items, to which 122 Latino participants with mental illness responded using a 7-point importance scale. Results showed item importance means ranging from 4.34 to 5.47, with counseling/therapy services and mental health treatment topping the list for healthcare needs. Analyses also examined differences between those born in the USA versus those born elsewhere. Latinos who were native to the USA differed significantly from those born abroad in over one quarter of importance ratings. Implications of these findings for integrated care of Latinos with serious mental illness are discussed.